Summer light, and then comes the night : a novel - Jón Kalman Stefánsson, 1963- (HarperVia, an imprint of HarperCollinsPublishers, 2021)
"Sometimes, in small places, life becomes bigger. Sometimes a distance from the world's tumult opens our hearts and our dreams. In a village of four hundred souls, the infinite light of an Icelandic summer makes its inhabitants want to explore, and the eternal night of winter lights up the magic of the stars. The village becomes a microcosm of the age-old conflict between human desire and destiny, between the limits of reality and the wings of the imagination. With humor, poetry, and a tenderness for human weaknesses, Stefánsson explores the question of why we live at all"--